Educar al algoritmo: Los imaginarios sobre la personalización en Spotify como forma de aprendizaje mediático. - ANGULO GRANDA, Andrea Teresa (Chasqui (13901079))
This article discusses how young people’s perceptions of Spotify’s music personalization represent forms of media literacy. To do so, this text will take as a base part of the results obtained in the research of the doctoral thesis: Jóvenes, música y algoritmos: análisis de la creación de sentido sobre el consumo musical por parte de Spotify y Youtube y los públicos juveniles published in 2024. Within this study, seven focus groups were conducted with adolescents and young people from 16 to 30 years old in Quito. As a result, the interactions, motivations and perceptions of audiences regarding the behaviors of algorithms were identified. In this text, these factors will be analyzed from the perspective of media literacy in order to identify strategies that young people carry out to face the datafication dynamics of music consumption.